EXPERIMENTAL RESEARCH OF FRACTURE TOUGHNESS ON NEW ROTOR STEEL FW2 AT ELEVATED TEMPERATURE - WU HaiLi; SUN LinGen (Jixie qiangdu)
The multi-specimen method and the normalization method and the elastic unloading compliance method were used to test the high-temperature fracture toughness of 630℃ on new rotor steel FW2. The multi-specimen method and the normalization method have obtained valid high-temperature fracture toughness test results. Comparison of the test results shows that the J-R resistance curve obtained by normalization method is within the ± 99.7% confidence interval of the fitting curve of the multi-sample method. The fracture toughness characteristic value J0.2 BL obtained by normalization method is lower than the characteristic value J0.2 BLobtained by the multi-specimen method and is located at the lower limit of the confidence interval of the multi-specimen method, which verifies the validity of the normalization method. Elastic unloading compliance method is not suitable for the high-temperature fracture toughness test for the stress field at the crack tip of FW2 steel does not conform to the elastic-plastic fracture mechanical characteristics at elevated temperature.